Efeitos inibitórios de extrato de casca de pinhão (Araucária Angustifolia) nas alfa-amilases salivar e pancreática - Silva, Simone Mariano da (2013)
Tannins are one of the most extensively studied molecules able to inhibit amylases. It is generally believed that the discovery of new materials rich in tannins with enzyme inhibitory properties can contribute for the discovery of new drugs useful in the control and treatment of diabetes, obesity and other physiological disorders. Araucaria angustifolia is a native conifer from South America, growing in southern and southeastern Brazil and northeastern Argentina. The pinhão coat is rich in tannins and up to now scarcely explored scientifically. The purpose of the present work was to investigate the possible effects of a pinhão coat extract rich in tannins on the activity of both the salivary and pancreatic α-amylases under in vitro and in vivo conditions. Al results obtained with the pinhão coat extract were compared with those obtained with a commercial tannin from Acacia mearnsii and with acarbose, a well known inhibitor of amylases. Human salivary -amylase and porcine pancreatic a-amylase were obtained from Sigma-Aldrich Co. The commercial tannin was purchased from Labsynth, Brazil. Acarbose was supplied by Sigma-Aldrich Co. The whole A. angustifolia seeds were cooked in water for 30 min in a pressure pot. After cooking, the seed coats were trimmed off and milled until fine powder. The seed coat powder was mixed with 70% ethanol (in water) at room temperature and mantained under agitation. The mixtures were filtered through Whatman filter paper number 1. The filtrate was concentrated with a rotary vacuum evaporator at 40 °C to eliminate ethanol and finally freeze-dried. The freeze-dried powders were stored in freezer until use. The kinetic experiments with the human salivary α-amylase were carried out at 40 oC in 50 mM Tris-HCl buffer pH 8.0 containing 10 mM EDTA and 1 mM sodium azide. The experiments with the porcine pancreatic ?-amylase were carried in 20 mM phosphate buffer, pH 6.9, containing 6.7 mM NaCl. Potato starch (Sigma-Aldrich) was used as substrate. Substrate and one of the three inhibitors, acarbose, commercial tannin or pinhão coat extract were mixed and the reaction was initiated by adding the enzyme. The reaction was allowed to proceed for 5 min. The produced reducing sugars were assayed by the dinitrosalicylic acid method, using maltose as standard. Male healthy Wistar rats weighing 200-250 g were used in all in vivo experiments. For oral starch tolerance test, rats were divided into 5 groups (n = 4 rats per group). To group I (positive control) commercial corn starch (1 g per kg body weight) was administered intragastrically. Group II (negative control) received only tap water. Group III received intragastrically commercial corn starch plus acarbose (50 mg/kg). Group IV received intragastrically commercial corn starch plus tannic acid (250 mg/kg). Finally, group V received intragastrically commercial corn starch plus pinhão extract (250 mg/kg). Fasting blood glucose levels were determined before the administration of starch and amylase inhibitors (0 time). Later evaluations of blood glucose levels took place at 15, 30, 45 and 60 min. Blood samples from the tail vein were analyzed by means of a glucometer...cont.